The acaricidal and repellent activity of the essential and nano essential oil of Thymus vulgaris against the larval and engorged adult stages of the brown dog tick, Rhipicephalus sanguineus (Acari: Ixodidae) - Zohreh Alibeigi; Ehsan Rakhshandehroo; Mohmmad Jamal Saharkhiz; Amir Mootabi Alavi (BMC Veterinary Research)
Abstract Background The brown dog tick is globally distributed and harms the host in terms of blood feeding and pathogen transfer. Chemicals are traditionally used for the control, but herbal plants have been investigated mainly due to their natural components with killing and repellant effects. Previously, the role of thymol has been described for the biocontrol of ticks at different stages. Therefore, a study was conducted to evaluate the effects of a thymol-rich herbal plant, Thymus vulgaris L., and its major constituents on Rhipicephalus sanguineus. Results In this work, we suggested performing the larval mortality test using 2 mL microtubes instead of previously described pocket and immersion methods. This method seems to be closer to the environmental condition. The results represented the great activity of the nano EO and thymol on live larva. The nano form caused 98.7% larval mortality at a low concentration of 0.25%. This effect reached 100% at 0.5% concentration, while the promising results for the EO was observed at 1 and 2% concentration showing 95.3 and 100% mortality, respectively. The nanoemulsion and thymol showed also a complete repellency effect against larva at the concentrations of 0.5% and 20 mg/mL, respectively. In adult tick bioassays, thymol was the only substance that accompanied by a statistically significant reduction in female oviposition rate (p < 0.05), however at its utmost concentrations of 20 and 40 mg/mL. Conclusion According to the results, the nano EO of T. vulgaris is recommended for the integrative control against R. sanguineus larva. In addition, further studies should be done on the nanomaterial to enhance its effect on adult female tick reproduction.